'A Healthy Sex Life': Love, Marriage and Sexual Knowledge in Franco's Spain (1960–1975). (11th February 2022) - García-Fernández, Mónica
Summary: This article aims to explore changes in the marital sex advice that was available in Spain during the last decade of the Franco Regime (1939–75). It pays particular attention to the representation of female sexuality, which was shaped by fluctuating ideas on the relationship between sexual pleasure, love and contraception. The study looks at a variety of sources and ponders the relationships between different types of discourses: male- and female-defined; religious and medical; popular and intellectual; expert and lay. These include marriage manuals, intellectual essays and women's magazines. These sources suggest that paying attention to the means by which sexual knowledge is conveyed, to the context in which it is disseminated, and to the subtle changes in the agents with the authority to communicate it gives us insight into how sexual knowledge is distributed, received and redefined.